Research on Vibration Characteristics of Propulsion Shafting Under Unbalanced-misaligned Coupling Fault. Issue 2 (March 2021) - Xu, Kai; Zhang, Yuqing; Ming, Tingfeng
Abstract: Vibration characteristics under unbalanced-misaligned coupling fault of propeller shaft were studied. Firstly, the rigid-flexible mixing model of propeller shaft system test bench is established by using Solidworks and ADAMS. Then, the shafting vibration characteristics in time and frequency domain are obtained by simulation analysis under normal, unbalanced, misaligned and unbalanced-misaligned coupling faults. Finally, the influence of rotational speed on unbalanced-misaligned coupling fault shaft system is analysed. The simulation study shows that the vibration spectrum of shafting under unbalanced-misaligned coupling fault is mainly the superposition of the spectrum under each single fault, and the vibration caused by each fault is different in different locations. The increase of speed will aggravate the vibration of shafting.